Formation of Calcium Vanadates by Solid State Reactions of V2O3 with CaCO3 - Li, Xinsheng; Xie, Bing (Asian Journal of Chemistry, 2012)
The chemical reactions in mixtures of solid V2O3:CaCO3 molar ratios of 1:1, 1:2 and 1:3 were investigated by XRD and TG-DSC. It was found that formation of calcium vanadates was dependent on the molar ratio of the starting materials and calcination temperature. Partial vanadium was transformed into the intermediate product Ca0.17V2O5 at 400 ºC. The V2O5 was produced at 500 ºC. Above 600 ºC, the calcium vanadates were formed. Ca(VO3)2 was formed in the mixtures with V2O3:CaCO3 molar ratios of 1:1 and 1:2 whereas CaV2O7 was formed in the mixtures with molar ratios of 1:1, 1:2 and 1:3 and Ca3(VO4)2 was formed in the mixtures with molar ratios of 1:2 and 1:3. With increasing calcination temperature, Ca(VO3)2 was transformed into Ca2V2O7 or even Ca3(VO4)2.